Peningkatan Keterampilan Menulis Cerita Pendek Menggunakan Pendekatan Saintifik Berbentuk Media Pop Up Pada Kelas VI SD Islam Pertiwi Nusantara Kota Makassar - Nurul Aqidah; Supriadi Supriadi; Erwin Nurdiasyah (STKIP Andi Matappa Pangkep, 2022)
This study aims to improve the learning process and short story writing skills using pop up media for sixth grade students of SD Islam Pertiwi Nusantara Makassar City. The design in this study uses a scientific model consisting of planning, implementation, observation, and reflection stages. The subjects of this study were the sixth grade students of Pertiwi Nusantara Islamic Elementary School, Makassar City, totaling 24 students. The object of this research is the skill of writing short stories. The method of data collection in this study used the methods of test, observation, and documentation. The data analysis technique used is qualitative techniques. The improvement of short story writing skills in the first cycle was 19.8 from the pre-cycle average score of 59.9 to 79.3. Meanwhile, the improvement of short story writing skills in the second cycle was 25.85 from the pre-cycle average value of 59.9 to 85.75.